A theoretical and experimental investigation of cutting forces and spring back behaviour of Ti6Al4V alloy in ultraprecision machining of microgrooves. (1st March 2020) - Zhao, Zejia; To, Suet; Zhu, Zhiwei; Yin, Tengfei
Highligths: Temperature evolution with cutting speeds is estimated by models. No phase transformation from α to β phase occurs in machining of seven grooves. Calculated cutting forces are in good agreement with the measurement. Equivalent shear stress increases with cutting speeds due to the high drag stress. More than 45% of the thrust force is derived from the spring back force. Abstract: Studying the material deformation is one of important research foundations in the machining process. In present work, material deformation and spring back behaviour of Ti6Al4V alloy were investigated in ultraprecision machining of seven microgrooves with gradually increased depth of cut to 5 μm. Material constitutive models and geometrical relationships are developed to estimate the temperature evolution, cutting forces, internals force/stress distribution and the spring back variation. The results show that no phase transformation from α to β phase occurs during micro groove machining according to the estimated temperature and experimentally observed microstructures. The calculated cutting forces are in good agreement with the experimental results at various cutting speeds within an error of about 3.53%. Though the increased temperature with the cutting speeds gives rise to low thermal and athermal stresses, the equivalent stress required to overcome the plastic flow of the Ti6Al4V workpiece increases with the speeds due to the high dislocation drag stress. In addition, more than 45% of the thrust force is derived from the spring back force, so the thrust force is significantly affected by the spring back in the machining of Ti6Al4V alloys. The theoretical analysis and experimental results provide potential benefits in predicting the cutting forces and controlling the spring back during machining of Ti6Al4V alloys. Graphical abstract: Image, graphical abstract